Towards the implementation of new European Bauhaus initiatives in circular cities programmes: analysis of best practices to identify investment sectors - Angrisano, M.; Gravagnuolo, A.; Bottero, M.; Fusco Girard, L. (Frontiers in Built Environment, 2025)
Climate change represents the most significant threat of the 21st century, exposing cities worldwide to a range of pressures which negatively affect citizens’ wellbeing and degradate ecosystem health. Circular economy principles emerge as a promising solution, offering innovative pathways to enhance city resilience, optimize resource use, and improve overall urban living conditions. This paper examines the integration of Circular Economy (CE) principles within the New European Bauhaus (NEB) framework, emphasizing their synergistic potential for promoting sustainable urban development. It provides foundational insights into the concepts of CE and NEB, establishing a comprehensive understanding of their interconnections. Using a mixed-method approach that combines inductive and deductive reasoning, the proposed study critically analyses various circular city programs to identify key investment sectors which align with CE and NEB objectives. Furthermore, this research sets the basis for a novel decision-support tool based on the identified investment sectors, aimed at facilitating the evaluation and implementation of urban transformation strategies that align with both CE and NEB paradigms. Therefore, the primary objective of this study is to offer cities and communities a structured framework that supports their transition toward sustainable, circular development, contributing to the creation of more resilient and inclusive urban environments.